Smart manufacturing technologies for industry 4.0 : integration, benefits, and operational activities - Kandasamy, Jayakrishna; Muduli, Kamalakanta; Meena, Purushottam L.; Kommula, V. P. (Boca Raton : CRC Press, 2022)
This book addresses issues related to the integration of digital evolutionary technologies and provides solutions to various challenges encountered during the implementation process. With real-time case studies, the book explains the smart technologies available and their operational applications and benefits in the manufacturing sector. Smart Manufacturing Technologies for Industry 4.0: Integration, Benefits, and Operational Activities assists in the understanding of the shifting paradigm in the manufacturing sector towards smart manufacturing and spotlights these technologies and the effects they are having on existing industries. It showcases Industry 4.0 as a promising research area in its infancy and offers insights into the role smart technologies are playing now and into the future. The book focuses on smart technologies' rudiments, implementation, and integration for organizational development and offers insights on how to achieve resiliency through and because of these technologies. This book presents real-time implementation discussions along with case studies that emphasize benefits and operational activities for engineers and managers. It's also a very useful book for technology developers, academicians, data scientists, industrial engineers, researchers, and students interested in uncovering the latest innovations in a field that seeks current research on products and services.
OCLC-licensed vendor bibliographic record.
Keywords: Manufacturing processes -- Automation; Manufacturing processes -- Technological innovations; Industry 4.0.; TECHNOLOGY / Manufacturing